SHEAR STRENGTH OF COMPACTED GREEN CLAY PHYSICO-CHEMICAL FACTORS - M. Omar; A. Shanableh; A. Tahmaz (Lowland Technology International, 2004)
Shear strength characteristics of Jordan’s green clay influenced by physico-chemical factors have been investigated. The investigation was carried out by subjecting soil to treatment by different cations namely, sodium, calcium, and potassium at three the pH-values (pH= 2.0, pH=7.0, pH= 12.0). Treated and untreated soils were tested at three different states on the compaction curve namely dry of optimum, optimum (= 12.5 kN/m³), and wet optimum. All specimens were tested for shear strength using unconsolidated undrained triaxial loading procedure. Test results indicated that shear strength of the natural soil was the highest in comparison with treated soils. In addition, K-treated soils showed the highest shear strength followed by the Ca-treated soil while, the Na-treated soil was the lowest in shear strength for all the states on the compaction curve except at the wet of optimum, where the Ca-treated soil was the highest in shear strength among all the treated soils. At pH=7.0 (Neutral state) the highest shear strength was recorded but as soils changed from acidic to basic shear, strength decreased accordingly.